An approach for preparing and responding to adverse events following immunization reported after hepatitis B vaccine birth dose administration. Issue 49 (17th November 2020) - Gidudu, Jane F.; Shaum, Anna; Habersaat, Katrine; Wilhelm, Elisabeth; Woodring, Joseph; Mast, Eric; Zuber, Patrick; Amarasinghe, Ananda; Nelson, Noele; Kabore, Hyacinte; Abad, Neetu; Tohme, Rania A.
Abstract: The success of immunization programs in lowering the incidence of vaccine preventable diseases (VPDs) has led to increased public attention on potential health risks associated with vaccines. As a result, a scientifically rigorous response to investigating reported adverse events following immunization (AEFI) and effective risk communications strategies are critical to ensure public confidence in immunization. Globally, an estimated 257 million people have chronic hepatitis B virus (HBV) infection, which causes more than 686, 000 premature deaths from liver cancer and cirrhosis. Hepatitis B vaccination is the most effective way to prevent mother-to-child transmission of HBV infection, especially when a timely birth dose is given within 24 h of birth. However, an infant's risk of dying is highest in the neonatal period, and thus, administering HepB-BD within 24 h of birth overlaps with the most fragile period in an infant's life. A working group formed in July 2016 following the publication of the case reports of the effects on vaccination coverage of media reports of infant deaths after HepB-BD administration in China and Vietnam. The goal of the working group was to create a framework and describe best practices for preparing for and responding to AEFI reported after HepB-BD administration, using existing resources. The framework includes six steps, including three preparation steps and three response steps. This document is written for national and regional immunization program staff. Prior to using the framework for preparation and response to AEFIs reported after HepB-BD administration, staff members should be familiar with how AEFI are detected, reported, and investigated in the country. The document might also be of interest to national regulatory staff members who monitor vaccine safety within the country.